Interatomic Coulombic decay of a Li dimer in a coupled electron and nuclear dynamics approach - Cabrera-Trujillo, Remigio; Vendrell, Oriol; Cederbaum, Lorenz S. (Physical review, 2020)
Interatomic Coulombic decay (ICD) is a fundamental process between atoms or molecules via a neighbor interaction that produces a relaxation of an electronically excited atom or molecule when embedded in an environment. Due to the physical nature of the process, the electronic and nuclear degrees of freedom are coupled. In this paper, we study the ICD process for a lithium dimer by means of the electron and nuclear dynamics (END) approach. The END approach incorporates a full time-dependent description of the electronic and nuclear degrees of freedom, although its current version does not properly account for continuum states and has limitations in the electronic description by using a single determinantal wave function. Despite this, we confirm that the ICD process takes place via a dipole interaction that induces the nuclear motion of the dimer with a consequent electronic population transfer to higher excited states simulating the ionization process. When the dimer approaches a distance of around 11.5 a.u. (6 angstrom), this ionization process takes place due to the dipole coupling and occurs at the place of the strongest attractive dipole force. Passing that point, we find that the two lithium atoms repel each other via a Coulomb explosion process followed with a consequent kinetic-energy release (KER). We determine the KER and the timing of the ICD process. We point out the strengths and weaknesses of the END approach and the required enhancements to account for a better description of the ICD process in a coupled electron and nuclear dynamics. Interatomic Coulombic decay (ICD) is a fundamental process between atoms or molecules via a neighbor interaction that produces a relaxation of an electronically excited atom or molecule when embedded in an environment. Due to the physical nature of the process, the electronic and nuclear degrees of freedom are coupled. In this paper, we study the ICD process for a lithium dimer by means of the electron and nuclear dynamics (END) approach. The END approach incorporates a full time-dependent description of the electronic and nuclear degrees of freedom, although its current version does not properly account for continuum states and has limitations in the electronic description by using a single determinantal wave function. Despite this, we confirm that the ICD process takes place via a dipole interaction that induces the nuclear motion of the dimer with a consequent electronic population transfer to higher excited states simulating the ionization process. When the dimer approaches a distance of around 11.5 a.u. (6 angstrom), this ionization process takes place due to the dipole coupling and occurs at the place of the strongest attractive dipole force. Passing that point, we find that the two lithium atoms repel each other via a Coulomb explosion process followed with a consequent kinetic-energy release (KER). We determine the KER and the timing of the ICD process. We point out the strengths and weaknesses of the END approach and the required enhancements to account for a better description of the ICD process in a coupled electron and nuclear dynamics.
Gesehen am 12.11.2020